(untitled) (Nonconventional Technologies Review, 2020)
In the paper, it is made a study to determinate the influences of different colour of resin in relation to the dimensional characteristics on the LCD photo polymerisation 3D printing process. In the first part are presented the element used to dimensional study and resins type and proprieties. In second part of the paper, it is possible to see the measurement methodology for dimension element and it is made the dimension measurement study and determinate the regression equations specific to each resins analysed. From the study, it is possible to see that the colour have an influence in direction of dimension in X and Y direction in horizontal or inclined position. The influence is greater in Y direction for different colour and lower in horizontal directing.